Hippocampal diffusion abnormality after febrile status epilepticus is related to subsequent epilepsy. (5th June 2019) - Yokoi, Setsuri; Kidokoro, Hiroyuki; Yamamoto, Hiroyuki; Ohno, Atsuko; Nakata, Tomohiko; Kubota, Tetsuo; Tsuji, Takeshi; Morishita, Masashi; Kawabe, Takashi; Naiki, Misako; Maruyama, Koichi; Itomi, Kazuya; et al.
Abstract: Objective: To assess hippocampal signal changes on diffusion‐weighted imaging (DWI) during the acute period after febrile status epilepticus (FSE) and to examine the relationship between DWI and subsequent epilepsy. Methods: A prospective, multicenter study of children with a first episode of FSE was performed. The patients underwent magnetic resonance imaging (MRI) within 3 days of FSE, and signal intensity was evaluated on DWI. Electroencephalography studies within 3 days of FSE were also assessed. Nine to 13 years after FSE, information on subsequent epilepsy was obtained. Results: Twenty‐two children with FSE were evaluated. DWI showed unilateral hippocampal hyperintensity in six patients (27%). Three of six patients with hippocampal hyperintensity had ipsilateral thalamic hyperintensity. On EEG within 3 days of FSE, five of six patients with hippocampal hyperintensity had ipsilateral focal slowing, spikes, or attenuation. Nine to 13 years later, the outcomes could be determined in five patients with hippocampal hyperintensity and in 10 without. All 5 patients with hippocampal hyperintensity had hippocampal atrophy and developed focal epilepsy, whereas only 1 of 10 patients without hippocampal hyperintensity developed epilepsy ( P = 0.002). Ictal semiology was concordant with temporal lobe seizures in all patients. Ipsilateral temporal epileptiform abnormalities were seen on EEG in four of five at last follow‐up. Significance: Acute DWI hippocampal hyperintensity was seen in 27% of patients with FSE. Acute DWI hyperintensity suggests cytotoxic edema caused by prolonged seizure activity. Hippocampal DWI hyperintensity is related to mesial temporal lobe epilepsy and can be a target of neuroprotective treatments to prevent the onset of epilepsy.